Factors Related to Seeking Health Services in People with Mental Disorders and Psychological Problems - Talia Puspita Adianti; Tusy Novita Dwi Wardani; Ratna Dwi Wulandari (Wolters Kluwer - Medknow Publications, 2022)
Introduction: Mental disorders are the inability to deal with stressors that interfere with social functions. The public health center seeks to improve the social functions of people with mental disorders (PWMDs) and psychological problems (PWPPs) through the integrated healthcare center. This study aimed to determine the effect of the ability to perceive, approachability, and health care needs on selecting health care facilities for PWMDs and PWPP. Methods: The research method used was observational with a cross-sectional design. The sampling technique was a multistage sampling technique with a stratified random sampling method. The research sample size was 16 public health centers, and the respondents were 177 families of PWMDs and PWPPs. The independent variables were the ability to perceive, approachability, and the need for health services. The dependent variable was the selection of health services. Data were obtained by the questionnaire and analyzed using the partial least square measurement. Results: A total of 59 families of PWMDs and PWPPs were categorized in the middle adulthood. Most of the people were male with mental disorders and psychological problems (63.1%) than the female gender (37.9%). The results of this study showed that the ability to perceive (11.622), approachability (3.903), and the need for health services (9.127) affect the desire for health services. Conclusion: The ability to perceive, approachability, and the need for health services significantly affect the desire for health services. Advocacy and health education are the necessary recommendations for handling mental health problems.